The promise of AUKUS: implications of its minilateral institutional form. - Chan, Lai-Ha; Rublee, Maria Rost (Australian Journal of International Affairs, 2024)
Much ink has been spilt over AUKUS, the new trilateral security partnership between Australia, the United Kingdom, and the United States in the Indo-Pacific, since its announcement in September 2021. In this article, we propose to examine AUKUS through the broader lens of its institutional form: a minilateral grouping. Using its institutional form as a basis for analysis allows us to move beyond particularistic analysis that is narrowly focused on specific aspects of the agreement such as the nuclear-powered submarines. We identify key benefits – efficiency and flexibility – and costs – political fragility and exclusion – of the minilateral institutional form generally, and then apply those benefits and costs to the case of AUKUS to examine to what extent the grouping may be able to contribute to the security interests of its three partners, as well as further peace and stability within the Indo-Pacific region. We find evidence for all four of these costs and benefits in the case of AUKUS. Of particular note is our finding that the risk of exclusiveness can generate resentment among allies and partners as well as adversaries, exemplified by the case of France.